Antynomie religii mitologicznej. Kilka uwag na marginesie Traktatu teologicznego Czesława Miłosza - Koehler, Krzysztof (Colloquia Litteraria, 2011)
The Noble Prize winner, Czeslaw Milosz in the last years of his life wrote a religious poem „The theological treatise”. In my paper I try to understand a religious dimension of a person who is the narrator of the poem. This is the voice of an experienced person who tries to find his way between two oppositions: the so called Polish catholicism (which is stereotypised as „mass” catholicism, unreflective, superficial etc) and a religion of a modern intellectual (with his religious hesitations, opposition to the catholic „mob” etc).I try to throw some light on a narrator’s perspective going back to some Molosz’s texts from the past. I hope the paper will be interesting to the scholars and others who are trying to solve the fascinating problem of the religious dimenssion of Czeslaw Milosz’s poetry.